Changes in the acoustic properties of road porous surface with time - GOŁĘBIEWSKI, Roman (Archives of Acoustics, 2008)
The low-noise surfaces such as porous asphalt have become more frequently used to reduce traffic noise. This method of noise control may be effective where reductions of the order of a few decibels are required, and may provide a more economic solution compared to other forms of noise control, such as noise barriers. The main disadvantage of the porous pavement is its decreasing acoustic effectiveness over time, caused by dirt blocking the pores on a road surface. The paper presents the acoustic effectiveness of the two types of porous road pavements after a few years of use.